Microplastic Pollution in Deep-Sea Sediments From the Great Australian Bight - Barrett, Justine; Chase, Zanna; Zhang, Jing; Holl, Mark M. Banaszak; Willis, Kathryn; Williams, Alan; Hardesty, Britta D.; Wilcox, Chris (Frontiers in Marine Science, 2020)
Interest in understanding the extent of plastic and specifically microplastic pollution has increased on a global scale. Still one large piece of the overall puzzle currently lacks: how much plastic pollution has found its way into the deeper areas of the world’s oceans? The extent of microplastic pollution in deep-sea sediments remains poorly quantified, but this knowledge is imperative for predicting the distribution and potential impacts of global plastic pollution. We quantified microplastics in deep-sea sediments from the Great Australian Bight using an adapted density separation and dye fluorescence technique. We analyzed sediment cores from six locations ranging in ocean depths from 1,655 to 3,062 m and offshore distances ranging from 288 to 356 km from the Australian coastline. Microplastic counts ranged from 0 to 13.6 fragments g-1 dry sediment (mean of 1.26 ± 0.68; n = 51). We found higher microplastic counts than recorded in other microplastic analyses of deep-sea sediments. Sample fragments were identified as polyisoprene, polyurethane, polyester, and polypropylene. A statistical analysis detected a relationship between sediment microplastic counts and the amount of plastic floating on the ocean surface above, as well as with the angle of the seafloor slope. The number of microplastic fragments in the sediment increased as surface plastic counts increased, and as the seafloor slope angle increased. Overall, however, the microplastic counts were highly variable, with variation between sediment cores at the same location being greater than the variation across the sampling sites. Our findings of microplastics in deep-sea sediment from the Great Australian Bight contributes to understanding where some of the ‘hidden’ oceanic plastic pollution is distributed.